Regression of hepatic fibrosis due to hepatitis C virus (HCV) infection and its associated factors in Mexican population treated with direct-acting antiviral agents. A preliminary study. - Raúl Ramírez-Marcial; Scherezada M. Mejía-Loza; María del Rosario Herrero-Maceda; Eumir Israel Juárez Valdes (Annals of Hepatology)
Introduction and Objectives: After achieving a sustained viral response with AAD, regression of fibrosis is not always achieved. Studies have been conducted to determine factors that may be involved such as age, BMI, diabetes, dyslipidemia, and steatosis, among others. OBJECTIVE: To determine the factors associated with regression of hepatic fibrosis in patients treated with AAD at the Juarez Hospital in Mexico. Materials and Patients: A retrospective, observational, cross-sectional study was conducted from January 2019 to March 2024 on patients diagnosed with hepatitis C virus infection. The following inclusion criteria were considered: Patients aged 18 or more who underwent treatment with sofosbuvir/velpatasvir 400mg/100mg for 12 weeks or glecaprevir/pibrentasvir 100mg/40mg for 8 weeks and had significant fibrosis (>F2) determined by FIB-4 score and APRI score before the treatment. Exclusion criteria: patients under 18 years of age, co-infection with HBV, and/or incomplete treatment. Patients were divided into 4 groups: GROUP 1: patients without hepatic cirrhosis and without associated comorbidities, GROUP 2: patients without hepatic cirrhosis but with associated comorbidities, GROUP 3: patients with hepatic cirrhosis without associated comorbidities, and GROUP 4: patients with hepatic cirrhosis and associated comorbidities. For each group, FIB-4 score and APRI score were measured at the beginning and after treatment to evaluate differences in fibrosis regression between groups. Results: 51 patients were recruited, of whom: 5 patients were part of Group 1. From this group, 40% achieved a decrease in stage APRI and FIB-4 stage after treatment. Group 2: 11 patients, 45% decreased one stage of APRI and FIB-4 score. Group 3: 19 patients, no patient achieved a decrease in APRI and FIB-4 score after treatment. Group 4: 16 patients, only 18.74% achieved a decrease in both APRI and FIB-4 stages after treatment, and the 25% of this group achieved a decrease just in APRI stage.. Conclusions: In this preliminary study, a major percentage of patients with and without hepatic cirrhosis plus another associated comorbidity (diabetes, hypertension, dyslipidemia, and/or hepatic steatosis) did not achieve a decrease in APRI and FIB-4 stages after treatment. Therefore, an analysis of variances should be performed to determine which of these factors impact fibrosis regression, and the sample size should be expanded to achieve significant results.